Entre a Pessoa e o Indivíduo: dilemas da sociologia relacional de Roberto DaMatta - Almeida, Alexandre Paz (2011)
This research seeks to build theoretical reflection on the meaning and importance of the concepts of "individual" and "person" in the relational sociology of Roberto DaMatta. The fundamental question that guides the study says that these concepts are fundamental and recurring, not only for the explanatory model of the sociology of Roberto DaMatta, but also for the Brazilian social thought, forming with other concepts (paternalism, personalism, tradition and modernity) a basic system for the interpretation of Brazilian society. In this sense, we seek to outline the meanings of concepts in the relational sociology of Roberto DaMatta as key categories in the process of explanation and understanding of Brazilian society, analyzing the logic and semantics of the concepts and the difference with other sociological interpretations. In this process of reflection was necessary to analyze critical about the work of DaMatta, especially those made by Jessé Souza.